The Roma Elite as an Upper Social Segment and its Role in Changing the Style of Life within Roma Population Communities - Elena Zamfir (Sociologie Românească, 2013)
The present study wants to bring a new approach of studying the Roma community based on a shift of perception which will end up depicting a completely new image of this population. We hoped that this survey of the upper social segment of the Roma – intellectuals, community leaders, and businessmen – would make a contribution to changing the negative perception of the Roma by the majority population. The objectives of my paper are closed related with some more important reasons of my previous survey approach of the Roma population: First, we wanted to create a more balanced and complete (self-) image of the Roma population and to change the perception of the majority population on the Roma people. This survey produced a more realistic and comprehensive image of different life situations present in the Roma community. Second, we wanted to create more optimism regarding the possibility to improve the life of the Roma and to motivate their actions towards overcoming underdevelopment using the power of their elite group. According to the C. Wright Mills ‘definition for the power elite, the success stories can become social models for the rest of the Roma community, proving the actual possibility of social mobility and success among Roma population. In this way, C. Wright Mills pointed out: “The power elite is composed of men whose positions enable them to transcend the ordinary environments of ordinary men and women; they are in positions to make decisions having major consequences” (Grusky and Szelenyi, 2007, 87). The success life stories can become social models for the rest of the Roma community, proving that social mobility and success are possible among the Roma. Third, the strategy of success by modernisation might consolidate the Roma's educational and professional outcomes, an important predictor of personal success in their professional career towards a highly desirable social status.